From Solidarity to Sellout - Kowalik, Tadeusz (Book collections on Project MUSE., 2012)
In the 1980s and 90s, renowned Polish economist Tadeusz Kowalik played a leading role in the Solidarity movement, struggling alongside workers for an alternative to "really-existing socialism" that was cooperative and controlled by the workers themselves. In the ensuing two decades, "really-existing" socialism has collapsed, capitalism has been restored, and Poland is now among the most unequal countries in the world. Kowalik asks, how could this happen in a country that once had the largest and most militant labor movement in Europe? This book takes readers inside the debates within Solidar